2019
DOI: 10.1002/jbmr.3732
|View full text |Cite
|
Sign up to set email alerts
|

Compromised Exercise Capacity and Mitochondrial Dysfunction in the Osteogenesis Imperfecta Murine (oim) Mouse Model

Abstract: Osteogenesis imperfecta (OI) is a heritable connective tissue disorder that most often arises from type I collagen—COL1A1 and COL1A2—gene defects leading to skeletal fragility, short stature, blue‐gray sclera, and muscle weakness. Relative to the skeletal fragility, muscle weakness is much less understood. Recent investigations into OI muscle weakness in both patients and mouse models have revealed the presence of an inherent muscle pathology. Understanding the mechanisms responsible for OI muscle weakness is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 69 publications
1
13
0
Order By: Relevance
“…It has consistently been shown as a protective mechanism in maintaining osteoblast viability by allowing cells to survive various stresses (Todde et al, 2009;White and Lowe, 2009;Gu et al, 2016;Yang et al, 2016;Zhu et al, 2019;Zhao et al, 2020). Furthermore, GC usage have been reported to inhibit osteoblast autophagy and this effect plays a pivotal role in the pathogenesis of GIOP (Han et al, 2018;Lian et al, 2018;Gremminger et al, 2019;Wang et al, 2019). Recently a specialized form of autophagy that specifically degrades dysfunctional or redundant mitochondria, termed mitophagy, was found to contribute to the mineralization function of osteoblasts (Pei et al, 2018a).…”
Section: Introductionmentioning
confidence: 99%
“…It has consistently been shown as a protective mechanism in maintaining osteoblast viability by allowing cells to survive various stresses (Todde et al, 2009;White and Lowe, 2009;Gu et al, 2016;Yang et al, 2016;Zhu et al, 2019;Zhao et al, 2020). Furthermore, GC usage have been reported to inhibit osteoblast autophagy and this effect plays a pivotal role in the pathogenesis of GIOP (Han et al, 2018;Lian et al, 2018;Gremminger et al, 2019;Wang et al, 2019). Recently a specialized form of autophagy that specifically degrades dysfunctional or redundant mitochondria, termed mitophagy, was found to contribute to the mineralization function of osteoblasts (Pei et al, 2018a).…”
Section: Introductionmentioning
confidence: 99%
“…The latest study on muscle function in oim/oim mice showed mitochondrial dysfunction in the gastrocnemius muscle, with decreased mitochondrial citrate synthase activity and respiration rates (34). While the connection between type I collagen alterations and mitochondrial function in muscle is not yet clear, this is an interesting and novel observation, and further studies are needed to validate this finding.…”
Section: Muscle Weaknessmentioning
confidence: 83%
“…Historically, muscle weakness in osteogenesis imperfecta has been attributed to hypoactivity, with patients reporting fatigue and reduced exercise capacity in addition to muscle weakness [ 6 , 30 ]. Studies in the homozygous osteogenesis imperfecta murine ( oim/oim ) model, which contains a nucleotide deletion in the Col1a2 gene resulting in nonfunctional proα2(I) collagen chains and the production of homotrimeric type I collagen [α(I) 3 ] rather than normal heterotrimeric type I collagen [α1(I) 2 α2(I)], were the first to demonstrate an inherent muscle pathology as part of the pathophysiology of OI [ 3 , 31 , 32 ]. Following this novel discovery, clinicians and basic scientists began to consider and investigate muscle function in OI patients and other mouse models of OI.…”
Section: Skeletal Muscle Weakness and Energy Metabolism In Oimentioning
confidence: 99%
“…In addition to reduced physical activity and skeletal muscle weakness, recent evidence in the Col1a1 Jrt/+ mouse suggests that metabolic perturbations exist, consisting of a hypermetabolic state with increased whole-body oxygen consumption and energy expenditures, potentially contributing to the pathophysiology of the disease [ 8 ]. Furthermore, a recent study in the homozygous oim/oim mouse demonstrated altered energy metabolism supported by increased energy expenditures in the oim/oim mice [ 9 ] and by skeletal muscle mitochondrial dysfunction, as evidenced by drastically reduced gastrocnemius mitochondrial respiration rates [ 32 ]. While there are limited studies evaluating energy metabolism in OI patients, a study by Cropp and Myers in 1972 described the presence of a hypermetabolic state in adolescent male OI patients [ 7 ].…”
Section: Skeletal Muscle Weakness and Energy Metabolism In Oimentioning
confidence: 99%
See 1 more Smart Citation